PENGARUH SENAM OTAK DAN BERMAIN PUZZLE TERHADAP FUNGSI KOGNITIF LANSIA DI PLTU JEMBER - SOFIA RHOSMA DEWI (JURNAL KESEHATAN PRIMER, 2016)
Introduction: Cognitive function consist of learning process, perception, understanding and rationalization. Most of elderly are facing declining cognitive function. This research is conducted to find out the effectiveness of combination of brain game and puzzle in order to increase elderly’s cognitive function. Method: It’s a pre experimental design with pre post test design. There were 48 respondents taken by purposive sampling. Respondents are given brain gym and and playing puzzle for 30 minutes, three days a week for a month. Cognitive function are measured by using MMSE before and after brain game. Result: Before treatment, 48 respondents show that all of them have moderate cognitive impairment. After treatment, 12 respondent show mild cognitive impairment and the rest show moderate cognitive function. The data analyzed by using Wilcoxon sign test and show p value 0,000 < α 0,05. Conclusion: Means that brain gym and puzzle are effective in order to increased or maintain elderly cognitive fuction.